Influence of field soil drought stress on some key physiological, yield and quality traits of selected newly-developed hexaploid bread wheat (Triticum aestivum L.) cultivars - Shahzad, Tariq; Muhammad Ashraf; Javaid, Muhammad Mansoor; Waheed, Hasnain; Abbas, Tasawer; Min Li, Min Li; Abdul Sattar (Penerbit Universiti Kebangsaan Malaysia, 2018)
Drought is one of the commonly occurring environmental stresses, limiting crop production in many countries. Selection of cultivar is the most effective and economical means for alleviating the adverse effects of drought stress on crops. The present study aimed to investigate the growth, some physiological processes, yield and quality of some newly-developed wheat cultivars (AARI-2011, AAS-2011, Faisalabad-2008, Millat-2011 and Punjab-2011) under field drought stress conditions. The cultivars were sown in a field under normal irrigation and drought-induced conditions. Maximum net photosynthetic rate was recorded in cv. AAS-2011 at growth stage of 67 days after wheat emergence under normal irrigation and cv. Faisalabad-2008 at 67 days after wheat emergence under drought condition. Leaf stomatal conductance and transpiration rate were maximum in cv. Faisalabad-2008 under drought conditions. The adverse effects of drought stress were observed more on cv. Millat-2011 than Faisalabad-2008, with respect to net photosynthetic rate and transpiration. Drought exerted a significant adverse effect on leaf stomatal conductance at 74 days after wheat emergence which was recorded as 230 mmol m-2 s-1. Among the cultivars, AAS-2011 recorded maximum yield traits and grain yield under normal irrigation condition and Faisalabad-2008 under drought condition. Cultivar Millat-2011 was the most susceptible to drought and Faisalabad-2008 the most resistant to drought. Faisalabad-2008 maintained the quality at the most under drought stress conditions. It is concluded that Fasialabad-2008 should be grown under field drought conditions to achieve maximal yield and quality of wheat.